2016
DOI: 10.18869/acadpub.johe.5.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of noise pollution on male fertility (Review)

Abstract: Background: Noise as a most common harmful physical agent in workplaces has some effects on the exposed persons such as hearing threshold reduction, increasing blood pressure, and interference with the speech. The adverse side-effect of noise is one of the scientific areas that have seldom been considered by researchers. The aim of this study was to investigate the effects of occupational noise on the male fertility (human and experimental animals) to be finally able to provide solutions for the future orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The study concluded that exposure to noise can affect testicular weight, sperm parameters (sperm count, vitality, mobility and morphology), sex hormone levels, testicular tissue and oxidative stress levels which in turn can be influential in male infertility. The present study [43] also found noise to be the main exposure variables that affects sex hormone levels.…”
Section: Noisesupporting
confidence: 72%
See 1 more Smart Citation
“…The study concluded that exposure to noise can affect testicular weight, sperm parameters (sperm count, vitality, mobility and morphology), sex hormone levels, testicular tissue and oxidative stress levels which in turn can be influential in male infertility. The present study [43] also found noise to be the main exposure variables that affects sex hormone levels.…”
Section: Noisesupporting
confidence: 72%
“…In a review study conducted in 2016 by Nadry et al the effects of noise on male fertility (human and lab animals) was investigated [43]. The study concluded that exposure to noise can affect testicular weight, sperm parameters (sperm count, vitality, mobility and morphology), sex hormone levels, testicular tissue and oxidative stress levels which in turn can be influential in male infertility.…”
Section: Noisementioning
confidence: 99%
“…The environmental causes of male infertility include prolonged exposure to heat [3], noise pollution [4], ionizing radiation [5], air pollution [6], mumps after puberty [7], alcoholism [8], and psychological stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the present study agrees with Chamkoory et al, in the case of reduced testosterone, LH, and FSH levels in those exposed to high levels of noise. Moreover, in a review study have been concluded that exposure to noise can affect testicular weight, sperm parameters (sperm count, vitality, mobility, and morphology), sex hormone levels, testicular tissue, and oxidative stress levels which in turn can be influential in male infertility (Nadri et al, 2016). These studies state that the mechanism of effect is dependent on the increase in stress hormone levels such as corticosterone and norepinephrine due to noise exposure and the resulting changes in the secretion of the leptin hormone which is an important hormone in metabolism and reproduction (Chandralekha et al, 2005).…”
Section: Noisementioning
confidence: 99%